Dinâmicas e demandas da Geração Z: da vida pessoal ao contexto profissional - Serafim, Júlia Neves (Brasil, 2024)
This paper investigates the perceptions and demands of Generation Z, focusing on the personal, contextual and professional dynamics that shape their choices and aspirations. The research uses a quantitative approach, applying structured questionnaires with a Likert scale to analyze variables such as parental support and pressure, the impact of the pandemic, flexibility at work and the search for purpose. The data analysis process involved descriptive analysis to understand the characteristics of the sample; then Cluster analysis (K-Means) was applied with the aim of identifying groups within Generation Z and examining their similarities and differences; finally, Spearman's Correlation was used to verify the relationships between the variables. The findings indicate that Generation Z values flexibility and a balance between personal and professional life, coupled with an appreciation of technology, which contributes to an increase in demand for innovative work environments, and an increase in this generation's preferences for hybrid and remote working models. Parental support was identified as a moderate influence, reflecting the pressure associated with expectations. Despite this, most of the sample showed less influence in relation to parental support.